The clinical value of fibrosis indices for predicting the hemorrhagic transformation in patients with acute ischemic stroke after intravenous thrombolysis - Chen, Jiahao; Li, Xiaoqin; Hu, Rui; Hu, Chuanchen (Frontiers in Aging Neuroscience, 2024)
BackgroundThe incidence of stroke in China is approximately 343 per 100,000 people each year, the highest rate worldwide. Hemorrhagic transformation (HT), particularly symptomatic intracerebral hemorrhage (sICH) following acute ischemic stroke (AIS) with or without intravenous thrombolysis (IVT), can lead to rapid neurological deterioration, poor prognosis, and even death. Non-alcoholic fatty liver disease (NAFLD) has been identified as a risk factor for stroke occurrence and associated with poor long-term functional outcomes. Nonetheless, no studies have examined the association between liver fibrosis and HT in AIS patients who underwent IVT.MethodA total of 826 patients with AIS who underwent IVT were included in this study. We calculated nine validated liver fibrosis indices to assess the extent of liver fibrosis. HT was detected by follow-up cranial CT/MRI within 24 h post-IVT and was classified as either hemorrhagic infarction (HI) or parenchymal hematoma (PH). Symptomatic intracranial hemorrhage was defined as a sudden symptomatic neurological deterioration, indicated by an increase in (National Institutes of Health Stroke Scale) NIHSS score of 4 points or more.ResultThe median values of fibrosis-4 (FIB-4), modified FIB-4 (mFIB-4), aspartate aminotransferase (AST)-platelet ratio index (APRI), Forns index, alanine aminotransferase (ALT)/AST (ARR), AST/ALT ratio-platelet ratio index (AARPRI), fibrosis quotient (FibroQ), and Fibrosis Index were significantly higher, while the fibrosis-5 (FIB-5) was significantly lower in the HT and sICH groups (all P < 0.001). After adjusting for potential confounders, all nine liver fibrosis indices remained associated with HT and sICH. Receiver operating characteristic (ROC) curve analysis revealed that the FibroQ score had the best predictive ability for HT (AUC = 0.707, CI = 0.652–0.762, P < 0.001), while FIB-4 had the best predictive ability for sICH (AUC = 0.802, CI = 0.711–0.892, P < 0.001).ConclusionLiver fibrosis, as validated by FIB-4, mFIB-4, FIB-5, APRI, Forns index, ARR, AARPRI, FibroQ, and Fibrosis Index, was associated with HT and sICH in AIS patients after IVT.